Cegah Risiko Tekanan Darah Tinggi Untuk Mengurangi Risiko Stunting Dengan Penerapan Pola Makan Yang Benar Dan Senam Hipertensi Didesa Sukasari Kec.Air Periukan Kab.Seluma - Inggani, Excelia Dwi; Habibi , Julius; Rossita , Taufianie; Sari , Yulan Okta; Uziman, Andes Mario (Utami Publisher, 2025)
Hypertension is measurement of systolic and diastolic blood pressure that continuously exceeds normal values. The prevalence of hypertension in Indonesia based on measurements of the population aged 18 years is 34.1%. Hypertension occurs in the age group 31-44 years 31.6%, 45-54 years around 45.3%, and at the age of 55-64 years 55.2%. The prevalence of hypertension in Indonesia is 34.1%. Bengkulu Province nationally ranks 26th at 28.14%, with an estimated number of cases ≥15 years. In Seluma Regency, Bengkulu Province, the incidence of Hypertension is quite high, there are Hypertension Cases, especially in the area of Dusun 1, Sukasari Village which is affected by a lack of diet and a lack of a healthy lifestyle. The 2025 Thematic Community Service Program (KKN-T) of Dehasen University Bengkulu focuses on efforts to prevent hypertension through an educational approach, namely with the method of hypertension counseling, implementation of good eating patterns and elderly gymnastics and distribution of leaflets and digital education. This activity was carried out through collaboration with village officials and the local community. The results of the activity showed an increase in public awareness regarding the importance of a clean and proper diet, reducing salt consumption, and utilizing elderly gymnastics in which the aim is to increase lung capacity and lower blood pressure. This program has proven effective as a community-based promotive and preventive strategy that can be a model for implementation in other areas. Cross-sector collaboration and ongoing education are very important to support efforts to reduce the incidence of hypertension, as well as contribute to preventing stunting by improving the health of the elderly and women of childbearing age.